A review of concentrated solar power status and challenges in India - Anil Kumar Yadav; Anil Kumar; Shailendra Sinha (Solar Compass)
Concentrated Solar Power (CSP) technology has emerged as a promising renewable energy solution, offering a sustainable and efficient means of electricity generation and thermal energy storage. India, endowed with abundant solar irradiance, has made significant strides in promoting CSP technology as part of its renewable energy portfolio. With a growing focus on reducing greenhouse gas emissions and enhancing energy security, the Indian government has initiated numerous policies, incentives, and projects to encourage CSP adoption. Parabolic trough collectors, a type of linear concentrating system, are currently in widespread use. Power or solar towers are the most common type of point concentrating CSP technology currently in use. India aims to achieve a renewable energy capacity of 175 GW by 2022, with solar power constituting 100 GW of the overall target. Concentrated solar power technology is slated to grow 87% during 2018–2023, 32% faster than in the previous five-year period 2012–2017 and reach 4.3 GW in 2023. In future, present review paper can be regarded as a valuable resource for researchers, policymakers and industry professionals seeking to comprehend the present condition of concentrated solar power in India. It can aid in the development of strategies to address obstacles and advance sustainable and efficient solar energy solutions.